Gender differences in nigrostriatal dopaminergic innervation are present at young-to-middle but not at older age in normal adults - Wong, Ka Kit; Müller, Martijn L.T.M.; Kuwabara, Hiroto; Studenski, Stephanie A.; Bohnen, Nicolaas I. (Journal of clinical neuroscience, 2012)
Gender differences in brain dopaminergic activity have been variably reported in the literature. We performed an evaluation for gender effects on striatal dopamine transporter (DAT) binding in a group of normal subjects. Community-dwelling adults (n = 85, 50F/35M, mean age 62.7 ± 16.2 SD, range 20-85) underwent DAT [ 11C]2-β-carbomethoxy-3β-(4-fluorophenyl) tropane (β-CFT) positron emission tomography (PET) imaging. Gender effects for DAT binding were compared using ANCOVA for two subgroups; young-to-middle aged adults and older adults, using an age threshold of 60 years. There were 54 subjects (24M/30F; mean age 72.9 ± 7.3) 60 years and older and 31 (11M/20F; mean age 45.0 ± 11.4) subjects younger than 60. Age-adjusted striatal DAT gender effects were present in the young-to-middle (F = 10.4, P = 0.003) but not in the elderly age group (F = 0.5, ns). Gender differences in nigrostriatal dopaminergic innervation are present, with higher levels of DAT binding in young-to-middle age women compared to men, but not present in the elderly.